Product development : a structured approach to consumer product development, design, and manufacture - Mital, Anil; Desai, Anoop (Elsevier, 2014)
Product development teams are composed of an integrated group of professionals working from the nascent stage of new product planning through design creation and design review and then on to manufacturing planning and cost accounting. An increasingly large number of graduate and professional training programs are aimed at meeting that need by creating a better understanding of how to integrate and accelerate the entire product development process. This book is the perfect accompaniment and a comprehensive guide.